Overexpression of Arginase 1 is linked to DNMT3A and TET2 mutations in lower-grade myelodysplastic syndromes and chronic myelomonocytic leukemia. (February 2018) - Cull, A.H.; Mahendru, D.; Snetsinger, B.; Good, D.; Tyryshkin, K.; Chesney, A.; Ghorab, Z.; Reis, M.; Buckstein, R.; Wells, R.A.; Rauh, M.J.
Highlights: Arginase activity/expression is elevated in lower-grade MDS and CMML patients. Myelomonocytic cells overexpress the anti-inflammatory enzyme ARG1. DNMT3A / TET2 mutations potentially drive an abnormal bone marrow immune environment. Abstract: Immune dysregulation is a common feature of myelodysplastic syndromes (MDS) and chronic myelomonocytic leukemia (CMML), particularly in early stages. However, the genetic basis remains poorly understood. We recently reported that macrophages from mice deficient in tet methylcytosine dioxygenase 2 ( Tet2 ), a model of MDS/CMML, are hyperinflammatory and have increased expression of arginase 1 ( Arg1 ). In macrophages and myeloid derived suppressor cells (MDSCs) expression of Arg1 contributes to T-cell suppression and immune evasion by L-arginine depletion, in the setting of chronic inflammation and cancer. Since human MDS and CMML are driven by TET2 mutations and associated with chronic inflammation, we hypothesized that arginase enzymatic activity and ARG1 expression would be increased in human MDS/CMML bone marrow. Elevated arginase activity was observed in bone marrow mononuclear cells of MDS and CMML patients with lower-grade features. Immunohistochemical studies confirmed that myelomonocytic cells overexpress ARG1. Additionally, mutations in the epigenetic regulators TET2 and DNMT3A corresponded to high ARG1 expression and activity. These findings suggest ARG1 is a biomarker of immune dysregulation in early MDS and CMML. Recent murine findings have implicated Tet2 and Dnmt3a in regulation of innate immunity. Our study suggests similar changes may be driven by human TET2 and DNMT3A mutations.